2017
DOI: 10.1016/j.jorganchem.2017.09.039
|View full text |Cite
|
Sign up to set email alerts
|

Packing polymorphism of dicarbonyl-[2-(phenylamino)pent-3-en-4-onato]rhodium(I)

Abstract: Packing in pairs, versus in linear arrays of [Rh(CH3COCHCN(Ph)CH3)(CO)2] Sigma-sigma interaction of rhodium molecular orbitals AIM bonding paths indicating intermolecular metallophilic Rh-Rh interactions NBO shows LP(Rh)-LP*(Rh pz) interaction Intermolecular rhodium-rhodium distance decreases with temperature

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Varshavsky reported the synthesis and properties of 2A [ 13 ] and related Rh-dicarbonyl complexes containing β-aminivinyl ketones [ 14 ]. The structure of 2B was confirmed by solid state crystal analysis [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Varshavsky reported the synthesis and properties of 2A [ 13 ] and related Rh-dicarbonyl complexes containing β-aminivinyl ketones [ 14 ]. The structure of 2B was confirmed by solid state crystal analysis [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of [Rh(CH 3 COCHCNHCH 3 )(CO) 2 ] 2A and [Rh(CH 3 COCHCNPhCH 3 )(CO) 2 ] 2B was performed as published in literature for 2B [ 15 ] and related complexes [ 16 ]. Di-µ-chloro-tetracarbonyldirhodium(I) (0.05 g, 0.1286 mmol) was dissolved in methanol (5 mL), and the ligand (0.2572 mmol), also dissolved in methanol (2 mL), was added dropwise over 10 min whilst stirring.…”
Section: Methodsmentioning
confidence: 99%
“…The distance between Rh2 and Rh2 0 is 3.3674(3) Å, which is within typical distances indicating Rh-Rh interaction (3.18-3.54 Å). [49][50][51][52][53][54][55] Indeed, Conradie et al reported that square-planar rhodium carbonyl complexes such as [(CO) 2 Rh(acac)] (acac = acetylacetonate) formed intermolecular rhodium chains by weak Rh-Rh interactions in a crystal packing system. [52][53][54][55] NMR analysis showed that the bis-dinuclear structure of 4 in the crystal structure should be maintained in the solution state.…”
Section: Resultsmentioning
confidence: 99%
“…[49][50][51][52][53][54][55] Indeed, Conradie et al reported that square-planar rhodium carbonyl complexes such as [(CO) 2 Rh(acac)] (acac = acetylacetonate) formed intermolecular rhodium chains by weak Rh-Rh interactions in a crystal packing system. [52][53][54][55] NMR analysis showed that the bis-dinuclear structure of 4 in the crystal structure should be maintained in the solution state. In the 13 C NMR spectrum, the signals derived from carbonyl groups coordinated to the Rh centers were observed at 181.7 ppm ( 1 J C-Rh = 74.7 Hz) and 181.3 ppm ( 1 J C-Rh = 74.4 Hz), which is consistent with the fact that Rh1 and Rh2 are non-equivalent in the solid state.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation